Homoserine and quorum‐sensing acyl homoserine lactones as alternative sources of threonine: a potential role for homoserine kinase in insect‐stage Trypanosoma brucei. Issue 1 (25th November 2014) - Ong, Han B.; Lee, Wai S.; Patterson, Stephen; Wyllie, Susan; Fairlamb, Alan H.
Summary D e novo synthesis of threonine from aspartate occurs via the β‐aspartyl phosphate pathway in plants, bacteria and fungi. However, the Trypanosoma brucei genome encodes only the last two steps in this pathway: homoserine kinase (HSK) and threonine synthase. Here, we investigated the possible roles for this incomplete pathway through biochemical, genetic and nutritional studies. Purified recombinant TbHSK specifically phosphorylates L‐homoserine and displays kinetic properties similar to other HSKs. HSK null mutants generated in bloodstream forms displayed no growth phenotype in vitro or loss of virulence in vivo. However, following transformation into procyclic forms, homoserine, homoserine lactone and certain acyl homoserine lactones (AHLs) were found to substitute for threonine in growth media for wild‐type procyclics, but not HSK null mutants. The tsetse fly is considered to be an unlikely source of these nutrients as it feeds exclusively on mammalian blood. Bioinformatic studies predict that tsetse endosymbionts possess part (up to homoserine in Wigglesworthia glossinidia) or all of the β‐aspartyl phosphate pathway (Sodalis glossinidius). In addition S. glossinidius is known to produce 3‐oxohexanoylhomoserine lactone which also supports trypanosome growth. We propose that T. brucei has retained HSK and threonine synthase in order to salvage these nutrients when threonine availability is limiting.